Modified Slide Culture Method for Faster and Easier Identification of Dermatophytes - YEVA ROSANA; TETSUHIRO MATSUZAWA; TOHRU GONOI; ANIS KARUNIAWATI (Indonesian Society for microbiology, 2014)
Basic slide culture as a morphological identification was known as the most common method for the identification of pathogenic mold fungi. This method preserved the morphological features relatively undisturbed compared with adhesive tape preparations. However, it was necessary to modify method of basic slide culture to improve its usability and shorten the time it needed to identify mold fungi. There were four kinds of method carried out in this study; two kinds of modified slide culture, one kind of direct culture on slant agar plate, and a basic slide culture for identifying mold fungi, which result would be compared with each other. These four methods were tested to 4 species of dermatophytes which were known as mold fungi that could infect skin, hair, and nails in human; those were Trichophyton mentagrophytes, Microsporum canis, Microsporum gypseum, and Epidermophyton floccosum. Result of this study showed that both modified slide culture and direct culture on slant agar plate could visualize the structure of dermatophytes faster than basic slide culture method. These methods were also easier to prepare compared to basic culture method. Conclusion of this study showed that basic slide culture method needed to be modified for better identification of mold fungi.